2010
DOI: 10.1186/1471-2369-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of mortality after acute kidney injury in patients with sepsis: a contemporary analysis

Abstract: Background: Acute kidney injury (AKI) is associated with increased short-term mortality of septic patients; however, the exact influence of AKI on long-term mortality in such patients has not yet been determined. Methods:We retrospectively evaluated the impact of AKI, defined by the "Risk, Injury, Failure, Loss of kidney function, End-stage kidney disease" (RIFLE) classification based on creatinine criteria, on 2-year mortality in a cohort of 234 hospital surviving septic patients who had been hospitalized at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 32 publications
2
54
1
Order By: Relevance
“…However, despite being the largest study of AKI in the setting of CAP, this study was still underpowered to detect small but clinically meaningful benefit of statin use. Given that sepsis is a leading cause of AKI (2,4,33) and that there are no specific therapies to improve outcomes from AKI, our findings may warrant further evaluation in larger studies. Because several statin trials are underway or are being planned in various patient population, our study is likely to inform such trial design.…”
Section: Discussionmentioning
confidence: 90%
“…However, despite being the largest study of AKI in the setting of CAP, this study was still underpowered to detect small but clinically meaningful benefit of statin use. Given that sepsis is a leading cause of AKI (2,4,33) and that there are no specific therapies to improve outcomes from AKI, our findings may warrant further evaluation in larger studies. Because several statin trials are underway or are being planned in various patient population, our study is likely to inform such trial design.…”
Section: Discussionmentioning
confidence: 90%
“…These results raise the possibility that AKI is a major contributor to both morbidity and mortality after combat injury. Furthermore, because increasing evidence suggests that an episode of AKI increases the risk for long-term mortality and CKD (18)(19)(20)(21)(22)(23), these results raise that possibility that future complications may be seen in patients who survive their initial hospitalization. Although AKI has been associated with increased mortality in large ICU cohorts (5,6), these patients differ from our study population: They were older, had more comorbid conditions, and had medical causes for their AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, AKI was still independently associated with death, as it is in non HIV-infected ICU patients (Odds ratio 4.21; 95% Confidence interval). In a study on the long-term risk of mortality after AKI in patients with sepsis, HIV infection was not associated with increased 2-year mortality after discharge from the ICU (Lopes et al, 2010). This study, however, made no comparison between the in-ICU survival of HIV-infected patients who developed AKI associated with sepsis, and HIV non-infected patients.…”
Section: Discussionmentioning
confidence: 85%
“…Another assessed the application of the RIFLE criteria for acute renal failure in critically ill HIV-infected patients, as well as their survival, but failed to compare it to the uninfected patients in their ICU, and was discarded as well (Lopes et al, 2007a). An article evaluating long-term risk of mortality after AKI in patients with sepsis was discarded because it only assessed the mortality of the group surviving ICU admission two years after their discharge (Lopes et al, 2010). The remaining two articles assessed the impact of acute renal failure on the HIV population in ICU retrospectively as single unit studies and identified it as a cause for increased mortality, but failed again to compare their outcomes with outcomes of patients from the general population with acute renal failure in ICU (Coquet et al, 2010;Lopes et al, 2007b).…”
Section: Resultsmentioning
confidence: 99%